Enhanced impingement cooling of a circular jet using a piezoelectric fan. (September 2019) - Zhou, Wenwu; Yuan, Lin; Wen, Xin; Liu, Yingzheng; Peng, Di
Highlights: An active piezoelectric jet that can be actuated in demand was proposed in the study. Heat transfer results demonstrated a maximum enhancement of 21%. The turbulent kinetic energy of piezoelectric jet was significantly intensified at a small gap. The vibrating piezoelectric fan greatly promoted the heat transfer within the wall and jet. Abstract: The present study explored and examined the piezoelectric (PE) jet: an active cooling concept that can be actuated in demand, which had an oscillating flow and extremely low power consumption. The heat transfer and flow characteristics of the PE jet were quantified at various Reynolds numbers ( Re = 5000, 10, 000, 18, 000) and spacings ( H / D = 4.5, 5.5, 6.5; corresponding gap G / D = 0.1, 1.1, 2.1). The temperature sensitive paint technique was used to study the heat transfer, and the particle image velocimetry technique was applied to resolve the flow characteristics and to further correlate the heat transfer results. Measured results show that the impingement cooling of the PE jet increased as the Re increased and as the H / D decreased. Compared with a circular jet, the PE jet exhibited a greatly improved heat transfer at H / D = 4.5 (i.e., G = 0.1 D ), with a maximum of 20% enhancement in area-averaged Nu . Due to the fan oscillation, the turbulent kinetic energy level in the PE jet was significantly higher than in the circular jet, which greatly promoted the heat transfer at a narrow gap. In general, the new PE jet can provide superior heat transfer performance at a small gap and a high Reynolds number.